SELF_REGULATED LEARNING MAHASISWI DITINJAU DARI STATUS PERNIKAHAN (Departement of Psychology, Faculty of Education, Universitas Negeri Semarang, 2012)
The ability of each individual is different in set up time and plan a learning activity. So is the student who has been married to a student who is not married, where students who are married have a dual role as a housewife is as well as students, while students who are not married only a student only. This self-regulation is the major difference in the learning process is often called SRL (self-regulated learning) between a student who is not married with a married. This type of research is comparative descriptive. This study uses proposive sampling techniques in sample collection. Its population is all students in the FIP either unmarried or married. The variables in this study are self-regulated learning and student status. Methods of data collection in this study using a scale of psychology as much as 58 item scale SRL. Methods of data analysis in this study using t test technique Test the validity of using the product moment calculations were performed using SPSS 17 for Windows and validity coefficients obtained between 0.282 to 0.788 and the test reliability was calculated with SPSS 17 using Cronbach Alpha calculation, produced 0.977. Hypothesis testing using t-test analysis showed that p = 0.247> 0.05 means that there are significant differences in self-regulated learning among students who are not married to a married student. Students who are not married have higher levels of SRL in the category by the number of 15 persons (36.3%), the category was 25 people (60.6%), and the lower categories of 1 person (2.4%), whereas the student who has been married have high levels of SRL categories by the number of 4 persons (9.6%), the category was 26 people (62.8%), and low categories of 11 people (26.6%). The conclusion obtained is that there are differences in self-regulated learning among students who are not married to a married student. Unmarried student who has self-regulated learning is higher than a married college student, so that the student who has been married to further enhance its ability to develop SRL in order to achieve the desired learning objectives.